(3QSGdI Ydi Hf YjSj aj eYQaI Yde GdGSWQdGHs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI Chd eG JMJGL Edjg ai Yde GdGSWQdGH eYQaI heYQaI CLRGA GdGQJaGY heYQaI GdMLQI heYQaI GdYfcHhJ s
(3BNQgG (B:s
(3eYQaI WGdY GdSfI hgh Cf JYQa WGdY GdSfI GdeGVjI aJVY Jdc GdOQLI Ydi NW GdejRGf s
(3Vef eLehY , JQJjHgG (B: 7s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(3757) s
Keywords: (3eJaQbGJs